Analysis of cell surface proteins delineates a differentiation pathway linking endocrine and nonendocrine human lung cancers. - Goodwin, G (1983)
We have previously determined that the cell surface protein phenotype distinguishes human small cell lung carcinoma (SCC), a neoplasm with endocrine properties, from non-SCC in culture. We now demonstrate that cloned cell cultures of human large cell undifferentiated lung carcinoma, established directly from a patient with mixed SCC and non-SCC, simultaneously express surface proteins characteristic of SCC and non-SCC lung cancer cells. Hence, SCC and a form of large cell carcinoma appear linked through a continuum of differentiation events that: (i) may explain clinically important transitions that occur between the major types of human lung cancer and (ii) provide evidence for a common cellular origin of endocrine and nonendocrine cells in the bronchial mucosa.